BALANCE SHEET EFFECT SEBAGAI PENENTU DETERMINAN STRUKTUR MODAL ENAM BURSA EFEK PADA NEGARA-NEGARA ASEAN - Zainal Abidin Sahabuddin; Stevanus Adree Cipto Setiawan (Media Riset Akuntansi, Auditing & Informasi, 2012)
Balance sheet effect is due to the relationship between the external and internalfactors. The purpose of this study is to obtain the result: firm size, firm growth, financial risk, asset structure, non debt tax shield on capital structure; influence of internal factors, the influence of internal and external factors of the company’s capital structure. The research was conducted in countries of ASEAN6, namely Indonesia, Malaysia, Philippines, Singapore, Thailand and Vietnam. Unit of analysis of this study is that corporations have huge capitalization in 2008 until 2011. Data analysis using regression method Simultaneous and panels. The results showed: the size of the company has a positive and significant impact on the capital structure for ASEAN6 countries; growth has a negative and significant impact on the capital structure in the country of Malaysia, the Philippines, and Thailand; financial risk has a negative and significant impact on the capital structure in Singapore , asset structure has a positive and significant impact on the capital structure for Singapore, Malaysia, and the Philippines; non-debt tax shield and a significant negative effect on the capital structure for the State of Indonesia and Malaysia, the interest rate has no significant effect on the capital structure in cASEAN 6 countries; foreign exchange rate has a positive and significant effect for the Philippines; rate of inflation on capital structure has a negative and significant impact to the state of Indonesia, the Philippines, and Vietnam while Malaysia, Thailand and Singapore have a positive and significant impact; economic growth on the capital structure has a negative and significant impact to the state of Indonesia, the Philippines, and Vietnam while Negara Malaysia, Thailand and Singapore have a positive and significant impact; contained internal influence on the capital structure for six ASEAN countries; There are internal and external influences on capital structure for ASEAN6 countries.